2015
DOI: 10.1590/1982-021620151756015
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades comunicativas e lexicais de crianças com Síndrome de Down: reflexões para inclusão escolar

Abstract: Resumo: OBJETIVO: verificar o desempenho comunicativo e lexical expressivo de crianças com Síndrome de Down e refletir sobre como a compreensão de fatores interferentes no processo de aprendizagem pode contribuir para uma melhor adaptação dessas crianças no ambiente escolar. MÉTODOS: a amostra proposta foi de 60 crianças, porém, após análise dos critérios de inclusão, participaram 20 crianças, 10 com Síndrome de Down e 10 com neurodesenvolvimento típico, de idade entre 36 a 62 meses, pareadas quanto ao gêner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
3
0
3
Order By: Relevance
“…This fact points out the need for more in-depth research regarding reference values in different regions, since variations in spoken Portuguese in each region (in Brazil and Portugal) can affect children's performance in specific semantic fields. Therefore, the vocabulary test showed good internal consistency and it was able to point out the lexical performance of the children evaluated, which had already been confirmed in Brazilian studies with populations in typical and altered language development (4,(8)(9)(10)(11)(18)(19)(20)(21) . In this way, its use seems to have the potential to quantify the vocabulary of children in early childhood (5 and 6 years old) who are speakers of European Portuguese, which may contribute to the area of language, given the scarcity of tests that allow the evaluation of children with this age group in Portugal.…”
Section: Discussionsupporting
confidence: 56%
“…This fact points out the need for more in-depth research regarding reference values in different regions, since variations in spoken Portuguese in each region (in Brazil and Portugal) can affect children's performance in specific semantic fields. Therefore, the vocabulary test showed good internal consistency and it was able to point out the lexical performance of the children evaluated, which had already been confirmed in Brazilian studies with populations in typical and altered language development (4,(8)(9)(10)(11)(18)(19)(20)(21) . In this way, its use seems to have the potential to quantify the vocabulary of children in early childhood (5 and 6 years old) who are speakers of European Portuguese, which may contribute to the area of language, given the scarcity of tests that allow the evaluation of children with this age group in Portugal.…”
Section: Discussionsupporting
confidence: 56%
“…Language is a fundamental ability to mediate social, school and learning skills, however, children with Down syndrome may have deficiency in reception and expression and require more stimulation in this area. A study that compared the expressive communicative and lexical performance of children with Down syndrome and children with typical development showed that the former presented lower results in the aspects of word and phrase production, narrative, time attention and naming figures (Lamônica & Ferreira-Vasques, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Destacando sobre a inclusão da pessoa com SD, é importante ressaltar que ela inicia-se no âmbito familiar, pela aceitação da criança, também na instituição escolar quando a criança começa a frequentá-la, pois ela se torna um dos primeiros ambientes em que a criança tem interação com outras pessoas, sendo crianças e adultos. (KESSLER, 2017, p. [15][16].…”
Section: Alterações Cognitivas E Cinesiofuncionaisunclassified